Students’ Participation in a Social Media Enhanced Learning Environment - Tervakari, Anne-Maritta; Silius, Kirsi; Kailanto, Meri (International Journal of Emerging Technologies in Learning (iJET), 2013)
In this article, we introduce the results of a study concerning visualizations of studentsâ?? participation and activity in TUT Circle, a social media enhanced web service for learning, networking, and communication. Well-designed visualizations can provide useful information for teachers to improve pedagogical practices and the quality of online courses. Visualization enables students to monitor their own activity levels and performance processes, and make strategic adjustments to improve them.